The Tourist Offer of the Whiteley Museum and its Surrounding Area on the Lower North Shore : A Quality Improvement Report - Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
This report analyzes the tourist offer in the eastern part of Quebec’s Lower North Shore, particularly the municipality of Bonne-Espérance, a region where English speakers make up the majority of the population. It focuses specifically on an institution in one of these municipalities, the Whiteley Museum. The report provides the authors’ suggestions to improve tourism development as a means to diversify the economy, potentially help reverse demographic decline, and build community vitality.

Feasibility Study for a Rapid Maritime Link for Passengers of the Lower-North-Shore - Conseils & Stratégies pour l'Avenir des Régions (PAR) (2013)
This study relates to the feasibility of a maritime link for passengers on the Lower North Shore aiming at meeting a need shown for accessibility of both citizens and tourist alike with an affordable, rapid link with improved frequency, between the different communities and lasting the summer period, departures from Natashquan and Blanc-Sablon.